Trends and implications of binge-watching on UiTM students / Ku Nur Nasreyzza Ku Nasri - Ku Nasri, Ku Nur Nasreyzza (2022)
The outbreak of the COVID-19 pandemic in March 2020 forced many people to stay at home for a lengthy period, and created new habits among television audiences. With television content being a dominant source of entertainment, the habit of binge watching among audiences has begun to take root. Binge-watching is a style of television watching that continues for several hours. It became a prominent phenomenon after the advent of Netflix. Netflix is an online video streaming service that offers users easy access to films, TV shows, and documentaries. Nonetheless, this habit of binge-watching Netflix content began to affect its users. This study focuses specifically on the effects for students from the Faculty of Film, Theatre, and Animation, UiTM. Based on the Uses and Gratifications Theory (UGT), this study aims to identify the watching habits among these university students, analyse the antecedents of the online video streaming of Netflix content, as well as evaluate the consequences of this binge-watching habit on the students. The data was obtained through an online survey, and a descriptive analysis was conducted to analyse and evaluate the data. The outcomes of this study show that students who binge-watched for hours during the outbreak were able to influence their watching habits and acknowledge a variety of antecedents and consequences of binge-watching on Netflix.